2014
DOI: 10.1093/toxsci/kfu213
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib Reduces the Rate of Dark Adaptation in the Rat Retina Independent of ALK Inhibition

Abstract: Crizotinib (Xalkori) is a tyrosine kinase inhibitor of both anaplastic lymphoma kinase (ALK) and mesenchymal-epithelial transition factor (c-Met). Though not predicted from standard nonclinical toxicological evaluation, visual disturbance became a frequently observed adverse event in humans. To understand the possible mechanism of this vision effect, an in vivo electroretinogram (ERG) study was conducted to assess retinal functional changes following oral administration of crizotinib. Immunohistochemical (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Therefore, the high frequency of visual disorder induced by crizotinib is unlikely to be attributable to ALK inhibition. This idea is consistent with previous findings indicating that an ALK-selective inhibitor did not produce significant changes on an electroretinogram [ 29 ]. Crizotinib also inhibits MET and ROS1 at nanomolar concentrations [ 25 ], while the inhibitory actions of alectinib on MET and ROS1 only occur at micromolar concentrations or higher [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the high frequency of visual disorder induced by crizotinib is unlikely to be attributable to ALK inhibition. This idea is consistent with previous findings indicating that an ALK-selective inhibitor did not produce significant changes on an electroretinogram [ 29 ]. Crizotinib also inhibits MET and ROS1 at nanomolar concentrations [ 25 ], while the inhibitory actions of alectinib on MET and ROS1 only occur at micromolar concentrations or higher [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed the expressions of ALK , MET , and ROS1 mRNA (receptor tyrosine kinases that serve as therapeutic targets in non-small-cell lung cancers [ 19 , 28 ]), in the mouse retina ( Fig 3 ). Immunoreactivity for ALK protein has been observed in mice [ 29 ]. Both crizotinib and alectinib inhibit ALK at nanomolar concentrations, but the incidence of visual disorder is higher for crizotinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alectinib is a selective ALK inhibitor with little or no 17 days later, after alectinib discontinuation and institution of steroid therapy (d), showed diffuse ground glass opacities and infiltration in both lungs and their attenuation, respectively inhibitory activity for other protein kinases, whereas crizotinib inhibits multiple tyrosine kinases including ALK, ROS1, and MET. This difference may contribute to differences in the incidence of side effects such as visual disorders between crizotinib and alectinib [9]. On the other hand, the present case shows that ILD is induced by alectinib as well as by crizotinib, suggesting that ALK inhibition itself is a cause of ILD.…”
Section: Discussionmentioning
confidence: 51%
“…Notably, crizotinib is a multiple small-molecule inhibitor of ALK, MET and ROS1. Liu et al [ 34 ] suggested that the peripheral edema was more common in c-MET inhibition compared to crizotinib. As what mentioned before, this adverse event was observed significantly less in a Phase I study of ceritinib, as well as alectinib, which more specifically inhibits ALK without inhibition of c-MET [ 33 ].…”
Section: Discussionmentioning
confidence: 99%